GENDER DIFFERENCE IN ACHIEVEMENT AND INTEREST OF STUDENTS EXPOSED TO CONCEPTS IN BLOCKLAYING, BRICKLAYING AND CONCRETING USING VIDEOTAPED AND TEXT-BASED COMPUTER ASSISTED INSTRUCTION - D, Ibrahim; R, Emmanuel; J, Ohize E (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
This study was designed to investigate gender differences in the achievement and interest of students in Blocklaying, Bricklaying, and Concreting using Videotaped and Text-based Computer Assisted Instruction (CAI). Quasi-experimental design of pre-test, the post-test group was adopted. 190 students from Niger state constituted the population specifically, 93 students from treatment group A (Videotaped CAI) while 97 students constituted the treatment for group B (Text-based CAI). Two research questions and two null hypotheses were developed to guide the study. The instruments for data collection were Blocklaying, Bricklaying, and Concreting Achievement Test (BBCAT) and Blocklaying, Bricklaying and Concreting Interest Inventory (BBCII). The instrument was validated by five experts from the Industrial and Technology Education Department, Federal University of Technology, Minna. The reliability coefficient of BBCAT was found to be 0.96 using Pearson Product Moment Correlation while the internal consistency of the BBCII items was found to be 0.83 using Cronbach Alpha. Mean and the standard deviation was used to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The study revealed that male students who taught BBC with videotaped CAI had higher mean scores than female students taught with Videotaped CAI in BBCAT. The study also revealed that female students taught BBC with text-based CAI had higher mean scores than male students taught with Text-based CAI in BBCAT. However, female students taught BBC with Videotaped CAI had higher mean scores than male students taught with Videotaped CAI in BBCII. Consequently, the researcher recommended that the National Board for Technical Education should consider it necessary in the curriculum content adaptation to computer-assisted instructional strategies for teaching BBC at technical colleges in the next review of the curriculum.